KAJIAN KAPASITAS PENGURUS GAPOKTAN PENERIMA DANA BLM-PUAP DALAM PENERAPAN MENTAL KEWIRAUSAHAAN DI KABUPATEN ENDE - Philipus N Supardi (AGRICA, 2017)
The Rural Agribusiness Development Program (PUAP) is one of the government programs that aim to improve the welfare of farmers. In its implementation, farmers who receive PUAP funds have not shown significant improvement in the welfare of farmers. One element that can maximize the utilization of PUAP funds is an entrepreneurial mentality at the farm level. The entrepreneurial mentality that is meant is; Instrumental traits, prestige traits, the nature of flexibility, the nature of risk-taking, self-control, the nature of hard work, the nature of self-confidence, the nature of hard work, innovative nature and cognitive nature. The population in this study was Gapoktan which had received PUAP funding assistance in 2010 in Ende districts as many as 30 gapoktan which were taken by random sampling (simple random) from 175 gapoktan in 21 sub-districts in Ende Regency, in measuring the data obtained, that is where indicators and parameters are measured using an ordinal scale, namely with a range of values ??1 to 5. Score 5 means very good, score 4 means good, score 3 means good enough, score 2 means not good and score 1 means not good. Based on the results of the study that the application of the entrepreneurial spirit possessed by the management of the PUAP capital recipient Gapoktan in Ende Regency, cumulatively included in the good category with an average value of 3.85. From the results of this cumulative value it shows that the Gapoktan administrators in Ende Regency are among those who are able to undergo entrepreneurial nature optimistically, not afraid to face risks, work hard and always believe in their own abilities without hesitation in acting, creative and innovative progress in business, and take advantage of opportunities related to the resources around them to support the success of the agribusiness they are undertaking.